2018
DOI: 10.3390/ijgi7110415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of User Performance in Interactive and Static 3D Maps

Abstract: Interactive 3D visualizations of geospatial data are currently available and popular through various applications such as Google EarthTM and others. Several studies have focused on user performance with 3D maps, but static 3D maps were mostly used as stimuli. The main objective of this paper was to identify differences between interactive and static 3D maps. We also explored the role of different tasks and inter-individual differences of map users. In the experimental study, we analyzed effectiveness, efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
1
24
1
Order By: Relevance
“…The suitability of selected methods of spatial data visualization and particular implementations significantly affect a user's ability to determine the correct information from a map. The quantification and evaluation of different factors affecting how information in a map is perceived by different user groups is the main task in many types of research [33][34][35]. Addressing modern trends in cognitive cartography and cartographic visualization methods can lead to insights in, and improvement to, cartographic production.…”
Section: Geovisualization Methodsmentioning
confidence: 99%
“…The suitability of selected methods of spatial data visualization and particular implementations significantly affect a user's ability to determine the correct information from a map. The quantification and evaluation of different factors affecting how information in a map is perceived by different user groups is the main task in many types of research [33][34][35]. Addressing modern trends in cognitive cartography and cartographic visualization methods can lead to insights in, and improvement to, cartographic production.…”
Section: Geovisualization Methodsmentioning
confidence: 99%
“…Thus, it becomes necessary to visualize the uncertainties of the 3D points, especially when those are derived from images dating from different periods. Several studies have shown that the accuracy of 3D geospatial data can be visualized in various ways, such as with heat maps or shading (Dübel et al, 2017;Herman et al, 2018;O'Banion et al, 2018;Zuk et al, 2005).…”
Section: Approach To Visualize Uncertaintiesmentioning
confidence: 99%
“…MacEachren et al, [21] stated that traditional geovisualizations and virtual environments are similar in terms of the use of realism. The suitability of the use of individual visualizations cannot be generalized and is dependent rather on the task type [22][23][24][25][26][27][28]. Opinions on how the level of realism influences human perception differ.…”
Section: Stimuli: Realism Vs Abstractionmentioning
confidence: 99%